General Ulysses S. Grant's Civil War Leadership: A Model for Indonesia's Sishankamrata Defense System - Octaviana, Shoraya Lolyta; Suadnyana, I Nyoman; Widjayanto, Joni; Harefa, Faonaso; Djoko Purwanto, Ignatius Eko (Lebah, 2025)
This study was motivated by interest in reviewing the combat experience of military figures General Ulysses S. Grant During the United States Civil War and its Devoted to Strengthening the System and Defense Doctrine Models in Indonesia that already exist; Sishankamrata. This study uses a mixed methods approach. The results showed that General Grant's combat experience in civil war in the United States had a significant influence on its success in winning the Mexican war, with a very strong correlation (R = 0.979). This finding can be interpreted that experience in the battlefield contributes greatly to forming strategic intuition, the effectiveness of decision making, and the ability of individual military leadership. The novelty of this study lies in the use of the Mixed Methods approach which integratively examines the relationship between combat experience and the development of military strategies in a historical and contemporary perspective. This study made an important contribution as a reference to the strengthening of the doctrine and implementation of the defense and security system of the people's universe (Sishankamrata) in Indonesia. The implications of this finding underline the importance of integration of experience -based learning in education and training in military leadership, the need to build military strategic leadership capacity that is not only based on theory, but the importance of empirical experience, both through military training, learning from war history, and combat operation experience. Suggestions for further research are that similar studies are carried out on more military figures from various so as to get a more comprehensive picture of how individual combat experiences can form adaptive military strategies so that it can be useful for strengthening the SishanKamrata model in Indonesia.